Extensión del rango distribucional de Funchalia woodwardi para el Pacifico Sureste (Decapoda, Dendrobranchiata, Penaeidae) - Guzman, Guillermo; Escribano, Rubén (Revista de Biología Marina y Oceanografía, 2019)
The occurrence of Funchalia woodwardi is reported for the first time for the Southeast Pacific region off the Chilean coast. Two specimens were collected during the program of scientific cruises to remote areas (CIMAR). The first specimen was collected in 1999 for the cruise CIMAR 5 station 21 (27°00’08"S-94°05’49"W) and the second specimen was collected in 2015 for the cruise CIMAR 21 station 11 (27°00’07"S-79°05’05"W) to oceanic Chilean island and represent the first record of this genus in the Pacific waters of America. With this new record the distribution of the species is pan tropical.